RESEARCH ON INDICATORS CHARACTERIZING THE MOVEMENT OF VEHICLE FLOWS ON MOUNTAIN HIGHWAYS (Innovate Conferences, 2025)
This article examines the characteristics of traffic on mountainous sections of roads in the conditions of the Republic of Uzbekistan, analyzes the intensity and composition of traffic flows, characteristics of road conditions, and road accidents.